Photophysics of Glycosylated Derivatives of a Chlorin, Isobacteriochlorin and Bacteriochlorin for Photodynamic Theragnostics: Discovery of a Two‐photon‐absorbing Photosensitizer1. (28th November 2013) - Aggarwal, Amit; Thompson, Sebastian; Singh, Sunaina; Newton, Brandon; Moore, Akeem; Gao, Ruomie; Gu, Xinbin; Mukherjee, Sushmita; Drain, Charles Michael
Abstract The photophysical properties of a chlorin, isobacteriochlorin and bacteriochlorin built on a core tetrapentafluorophenylporphyrin (TPPF20) and the nonhydrolyzable para thioglycosylated conjugates of these chromophores are presented. The photophysical characterization of these compounds was done in three different solvents to correlate with different environments in cells and tissues. Compared with TPPF20 other dyes have greater absorption in the red region of the visible spectrum and greater fluorescence quantum yields. The excited state lifetimes are from 3 to 11 ns. The radiative and nonradiative rate constants for deactivation of the excited state were estimated from the fluorescence quantum yield and excited state lifetime. The data indicate that the bacteriochlorin has strong absorption bands near 730 nm and efficiently enters the triplet manifold. The isobacteriochlorin has a 40–70% fluorescence quantum yield depending on solvent, so it may be a good fluorescent tag. The isobacteriochlorins also display enhanced two‐photon absorption, thereby allowing the use of 860 nm light to excite the compound. While the two‐photon cross section of 25 GM units is not large, excitation of low chromophore concentrations can induce apoptosis. The glycosylated compounds accumulate in cancer cells and a head and neck squamous carcinoma xenograft tumor model in mice. These compounds are robust to photobleaching.